Power-Constrained Fuzzy Logic Control of Video Streaming over a Wireless Interconnect. (23rd June 2008) - Razavi Razavi, Rouzbeh Rouzbeh; Fleury Fleury, Martin Martin; Ghanbari Ghanbari, Mohammed Mohammed
Abstract : Wireless communication of video, with Bluetooth as an example, represents a compromise between channel conditions, display and decode deadlines, and energy constraints. This paper proposes fuzzy logic control (FLC) of automatic repeat request (ARQ) as a way of reconciling these factors, with a 40% saving in power in the worst channel conditions from economizing on transmissions when channel errors occur. Whatever the channel conditions are, FLC is shown to outperform the default Bluetooth scheme and an alternative Bluetooth-adaptive ARQ scheme in terms of reduced packet loss and delay, as well as improved video quality.